Factors to improve organizational performance in PT Victorindo Pratama Mandiri in Medan - Widjaja, Dennis; Karo-karo, Alex P.; Tj, Martinus; Sunijati, Elisha; Anton, Anton (Institute of Computer Science (IOCS), 2025)
This study aims to see the improvement of employee performance influenced by leadership style and organizational culture where OCB (Organizational Citizenship Behavior) as an intervening variable because OCB is the behavior of employees who help each other where they work beyond their formal job responsibilities to support coworkers and improve the overall effectiveness of the company. Examples include offering assistance to coworkers, covering tasks during absences, and fostering a cooperative work environment. This study was conducted at PT. Victorindo Pratama Mandiri in Medan using a quantitative approach. The sample consisted of 153 employees selected through a random sampling technique based on the Slovin formula. Data collection was carried out using a survey, and This study was implemented with the Partial Least Squares Structural Equation Modeling method in - Path model expression modeling. The findings indicate that organizational culture and leadership style have a positive impact on leadership effectiveness, with OCB serving as a mediating variable. The model reveals a positive relationship between the variables, supporting the proposed hypothesis and aligning with the established theoretical framework.